Implementasi Metode Prototyping oleh Raymond McLeod pada Sistem Informasi Pelaporan Indikator Pelayanan Rawat Inap (Studi Kasus: RSUD dr. H. Moch. Ansari Saleh Banjarmasin) - Farraswati, Nabilah Metilina; Roziqin, Mochammad Choirur; Farlinda, Sustin; Muna, Niyalatul (Jurnal Kesehatan, 2023)
Indicators of inpatient services at RSUD dr. H. Moch. Ansari Saleh Banjarmasin was obtained from manual census recapitulation process based on the patient register book in each inpatient unit. After that, the data was processed by reporting officers in Sub Division of Medical Record. Based on that process, there are still problems so the guarantee of reports accuracy is not optimal and information cannot be available on time whenever needed. Therefore, a method with a research and development approach was applied to design and create an information system for reporting web-based inpatient service indicators at RSUD dr. H. Moch. Ansari Saleh Banjarmasin. That information system as a means of collecting and distributing daily inpatient census data to the Sub Divisions of Medical Record to minimize delays in processing reports and improve data accuracy. The system development method applied in this research is a prototype model from Raymond McLeod. This research uses interview, observation, focus group discussion and documentation techniques for data collection. The results of this research is a reporting information system with outputs census recapitulation based on inpatient room categories and functional medical personnel (SMF) categories, visit recapitulation based on patient payment and discharge methods, as well as inpatient service indicators consisting of BOR, AvLOS, BTO, TOI, Barber Johnson Graph, GDR and NDR based on inpatient room category and SMF category. In addition, the information system can also send reports automatically to the electronic mail address of those in need and send notifications to management if the value of inpatient service indicator doesn't meet the standard.